Communication Orientation and Child Marriage Preferences (A Study of Adolescents and Parents in Keliling Benteng Ulu Village) - Astinana Yuliarti; Yuanita Setyastuti; Muhammad Alif; Novaria Maulina; Samsir Eka Putera (Metacommunication: Journal of Communication Studies, 2026)
Child marriage remains a significant social issue in South Kalimantan Province, particularly in Banjar Regency. This study aims to analyze family communication orientation and child marriage preferences among Banjar ethnic communities in Keliling Benteng Ulu Village. Using Family Communication Pattern Theory (FCPT) as the main theoretical framework to understand family interaction dynamics, a qualitative descriptive approach was employed, with data collected through in-depth interviews with six informants (parents and childrens). The results indicate that family communication is predominantly characterized by a high conformity orientation, rooted in Islamic values and local cultural norms, positioning parents as the primary authority in family decision-making. However, this conformity orientation has adapted to contemporary social conditions through the adoption of more flexible communication strategies, such as the give and take approach and the use of local wisdom during family interactions. Child marriage preferences are constructed through shared meanings that emphasize cultural–religious legitimacy and economic readiness. This study concludes that efforts to prevent child marriage will be more effective when they are designed by strengthening family communication and integrating local cultural values, rather than relying solely on top-down normative approaches.